Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To solve the quadratic equation \(3x^2 + x - 5 = 0\), we will use the quadratic formula, which is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, the coefficients \(a\), \(b\), and \(c\) are:
\(a = 3\), \(b = 1\), and \(c = -5\).
First, we need to calculate the discriminant (\(\Delta\)), which is part of the quadratic formula under the square root. The discriminant is given by:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values of \(a\), \(b\), and \(c\):
[tex]\[ \Delta = (1)^2 - 4(3)(-5) \][/tex]
[tex]\[ \Delta = 1 - (-60) \][/tex]
[tex]\[ \Delta = 1 + 60 \][/tex]
[tex]\[ \Delta = 61 \][/tex]
The discriminant is 61. Since the discriminant is positive, we will have two distinct real roots.
Next, we calculate the roots using the quadratic formula. The two possible solutions are:
[tex]\[ x_1 = \frac{-b + \sqrt{\Delta}}{2a} \quad \text{and} \quad x_2 = \frac{-b - \sqrt{\Delta}}{2a} \][/tex]
Substituting the values of \(a\), \(b\), and \(\Delta\):
[tex]\[ x_1 = \frac{-1 + \sqrt{61}}{6} \][/tex]
[tex]\[ x_2 = \frac{-1 - \sqrt{61}}{6} \][/tex]
To find the approximate values of these roots, we will compute the value inside the square root and then evaluate the expressions:
[tex]\[ \sqrt{61} \approx 7.81 \][/tex]
Now substituting this approximation into the expressions for \(x_1\) and \(x_2\):
[tex]\[ x_1 = \frac{-1 + 7.81}{6} \approx \frac{6.81}{6} \approx 1.14 \][/tex]
[tex]\[ x_2 = \frac{-1 - 7.81}{6} \approx \frac{-8.81}{6} \approx -1.47 \][/tex]
Thus, the solutions to the quadratic equation \(3x^2 + x - 5 = 0\) are approximately:
[tex]\[ x_1 \approx 1.14 \quad \text{and} \quad x_2 \approx -1.47 \][/tex]
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, the coefficients \(a\), \(b\), and \(c\) are:
\(a = 3\), \(b = 1\), and \(c = -5\).
First, we need to calculate the discriminant (\(\Delta\)), which is part of the quadratic formula under the square root. The discriminant is given by:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values of \(a\), \(b\), and \(c\):
[tex]\[ \Delta = (1)^2 - 4(3)(-5) \][/tex]
[tex]\[ \Delta = 1 - (-60) \][/tex]
[tex]\[ \Delta = 1 + 60 \][/tex]
[tex]\[ \Delta = 61 \][/tex]
The discriminant is 61. Since the discriminant is positive, we will have two distinct real roots.
Next, we calculate the roots using the quadratic formula. The two possible solutions are:
[tex]\[ x_1 = \frac{-b + \sqrt{\Delta}}{2a} \quad \text{and} \quad x_2 = \frac{-b - \sqrt{\Delta}}{2a} \][/tex]
Substituting the values of \(a\), \(b\), and \(\Delta\):
[tex]\[ x_1 = \frac{-1 + \sqrt{61}}{6} \][/tex]
[tex]\[ x_2 = \frac{-1 - \sqrt{61}}{6} \][/tex]
To find the approximate values of these roots, we will compute the value inside the square root and then evaluate the expressions:
[tex]\[ \sqrt{61} \approx 7.81 \][/tex]
Now substituting this approximation into the expressions for \(x_1\) and \(x_2\):
[tex]\[ x_1 = \frac{-1 + 7.81}{6} \approx \frac{6.81}{6} \approx 1.14 \][/tex]
[tex]\[ x_2 = \frac{-1 - 7.81}{6} \approx \frac{-8.81}{6} \approx -1.47 \][/tex]
Thus, the solutions to the quadratic equation \(3x^2 + x - 5 = 0\) are approximately:
[tex]\[ x_1 \approx 1.14 \quad \text{and} \quad x_2 \approx -1.47 \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.